Clinical and molecular characteristics of HNSCC patients with brain metastases: a retrospective study - Bulut, Cem; Lindel, Katja; Hauswald, Henrik; Brandt, Regine; Klauschen, Frederick; Wolf, Janina Luisa; Wolf, Thomas; Plinkert, Peter K.; Simon, Christian; Weichert, Wilko; Stenzinger, Albrecht (European archives of oto-rhino-laryngology and head & neck, 2014)
Among the metastasis patterns of head and neck squamous cell carcinoma (HNSCC), intracranial spread is a rare but dreaded event. To date only very few cases have been reported and clinical and molecular data are sparse. We screened our archives for HNSCC patients from 1992 to 2005 who were diagnosed with brain metastases (BM). For retrospective analysis, all clinico-pathological data including disease-free survival (DFS), local progression-free survival (LPFS), and overall survival (OS) were compiled. Additionally, we assessed the mutational status of the TP53 gene and the prevalence of HPV serotypes by PCR and Sanger sequencing. Immunohistochemistry was applied to detect p16INK4A expression levels as surrogate marker for HPV infection. The prevalence rate of BM in our cohort comprising 193 patients with advanced HNSCC was 5.7 %. Of 11 patients with BM, 3 were female and 9 were male. Seven of the primary tumors were of oropharyngeal origin (OPSCC). LPFS of the cohort was 11.8 months, DFS was 12.1 months and OS was 36.0 months. After the diagnosis of BM, survival was 10.5 months. Five tumors showed a mutation in the TP53 gene, while five of the seven OPSCC tumors had a positive HPV status displaying infection with serotype 16 in all cases. Compared with patients who harbored TP53wt/HPV-positive tumors, patients with TP53 mutations showed a poor prognosis. Compared with the whole cohort, the interval between diagnosis of the primary and the detection of BM was prolonged in the HPV-infected OPSCC subgroup (26.4 vs. 45.6 months). The prognosis of HNSCC patients with BM is poor. In our cohort, most tumors were OPSCC with the majority being HPV positive. Our study points toward a putatively unusual metastatic behavior of HPV-positive OPSCC.
Published online: 29 August 2013
Gesehen am 04.12.2020